2014
DOI: 10.1002/cphc.201402266
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of One‐Dimensional Carbon: Polyynic versus Cumulenic

Abstract: A question of both fundamental as well as practical importance is the nature of one-dimensional carbon, in particular whether a one-dimensional carbon allotrope is polyynic or cumulenic, that is, whether bond-length alternation occurs or not. By combining the concept of aromaticity and antiaromaticity with the rule of Peierls distortion, the occurrence and magnitude of bond-length alternation in carbon chains with periodic boundary conditions and corresponding carbon rings as a function of the chain or ring le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
64
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 41 publications
3
64
0
2
Order By: Relevance
“…To examine the potential for polyyne bending, the group in Milan again figured prominently, and the polyynes Ad[n] ( Figure 5) were studied by IR and Raman spectroscopies, in both the solution and solid states. The solid-state IR spectra in Figure 9b show that mutual exclusion between Raman and IR lines is not upheld (see arrows), particularly for the longer polyynes, such as Ad [6]. This is not especially surprising, since inversion symmetry is Figure 9c).…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…To examine the potential for polyyne bending, the group in Milan again figured prominently, and the polyynes Ad[n] ( Figure 5) were studied by IR and Raman spectroscopies, in both the solution and solid states. The solid-state IR spectra in Figure 9b show that mutual exclusion between Raman and IR lines is not upheld (see arrows), particularly for the longer polyynes, such as Ad [6]. This is not especially surprising, since inversion symmetry is Figure 9c).…”
Section: Introductionmentioning
confidence: 68%
“…combining the concept of aromaticity and antiaromaticity with the rule of Peierls distortion". [6] These last [a] two points perhaps help to justify the inclusion of this perspective in a topical issue on aromaticity dedicated to Professor Nozoe.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although the Peierls distortion makes the polyynic structure being at the minimum of the potential energy and stretching enhances the Peierls transition, 12 zeropoint atomic vibrations eliminate the distortion and restore the cumulenic structure. 13 Electrical transport measurements of finite monatomic carbon chains have confirmed that the measurement conditions, including strain, have a decisive influence on their conductivity. 14,15 Furthermore, even when an ohmic behavior is observed in unstrained carbon chains, the measured conductivity is still much lower than the predicted theoretical value, illustrating the key role of the contacting leads.…”
Section: Introductionmentioning
confidence: 98%